Earth – Humanity – Sustainability – Future – Education - Demšar, Andrej (Wydawnictwo Politechniki Łódzkiej, 2022)
In the article author introduces the problems and challenges of current world concerning sustainability. We have one planet and we should take care of it. Unfortunately, we are exploiting the Earth natural resources as they were endless. We, as humanity, use all natural resources, available in one year, in half of year. The 6th mass extinction of the animal species has begun. Four reasons for the sustainability crisis are defined (world economic system, overproduction, consumerism and set of values). The solutions for the sustainability crisis should not use the same thinking which we used when we created it. The stakeholders who have the power to make a change are defined (consumers, economy, legislators). Examples of good practices are presented (Green deal, Patagonia). Education is introduced as the strongest tool to make a long-term and long-lasting change. Values for the future and competencies for the engineers of the future are also defined. At the end it is concluded that your role in creating a sustainable world is extremely important. Be courageous and search for the solutions outside of the established practices. Search for the solutions with experts from other disciplines – think and act transdisciplinary. Be aware of all possibilities – act holistically.
Keywords: earth; humanity; sustainability; future; education; holism; ziemia; ludzkość; zrównoważony rozwój; przyszłość; edukacja; holizm